Research on Digital Transformation Strategies of Small and Medium-Sized Enterprises - Jiang, Hao (Transactions on Economics, Business and Management Research, 2024)
This article delves deeply into the strategic paths of small and medium-sized enterprises (SMEs) in their digital transformation journey, focusing on the unique challenges and unprecedented opportunities they face. Comprehensive data analysis uncovers specific difficulties faced by SMEs in areas such as digital technology adoption, resource constraints, and market adaptability. At the same time, it highlights the vast potential of cutting-edge technologies like big data, cloud computing, and artificial intelligence to reduce costs, enhance efficiency, and expand market reach for these enterprises. By reviewing relevant literature from both domestic and international sources, this study paints a picture of the current landscape of digital transformation among SMEs in China and offers practical strategic suggestions tailored to their unique circumstances. These include customized technology solutions, leveraging government policy support, and fostering digital ecosystem collaborations, all aimed at empowering SMEs to overcome obstacles, fully embrace the digital age, and achieve sustainable growth and enhanced market competitiveness.